2022
DOI: 10.1021/acs.inorgchem.1c03453
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark Study on the Calculation of 119Sn NMR Chemical Shifts

Abstract: A new benchmark set termed SnS51 for assessing quantum chemical methods for the computation of 119Sn NMR chemical shifts is presented. It covers 51 unique 119Sn NMR chemical shifts for a selection of 50 tin compounds with diverse bonding motifs and ligands. The experimental reference data are in the spectral range of ±2500 ppm measured in seven different solvents. Fifteen common density functional approximations, two scalar- and one spin–orbit relativistic approach are assessed based on conformer ensembles gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 153 publications
0
32
0
Order By: Relevance
“…Upon heating the solution, the signal for 3 diminishes in intensity and a new signal appeared at δ=417.5 ppm (computational study revealed a δ calc . of 505.9 ppm for the dimer 2 ) [35, 36] . This new signal intensifies as the temperature is increased further.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Upon heating the solution, the signal for 3 diminishes in intensity and a new signal appeared at δ=417.5 ppm (computational study revealed a δ calc . of 505.9 ppm for the dimer 2 ) [35, 36] . This new signal intensifies as the temperature is increased further.…”
Section: Methodsmentioning
confidence: 87%
“…= À 340.1 ppm for 3). [35,36] Upon heating the solution, the signal for 3 diminishes in intensity and a new signal appeared at δ = 417.5 ppm…”
Section: Methodsmentioning
confidence: 99%
“…In standard quantum chemical problems, the nonrelativistic Schrödinger equation is approximately solved to obtain the final wave function. However, relativistic effects can affect the molecular geometry as well as properties, especially when heavy atoms (typically with Z > 36) are present. They can be included implicitly by relativistic effective core-potentials (ECPs) that replace the core electrons. This approach has the advantage of a lower computational cost and is sufficient for most chemical problems which mainly depend on valence electrons like thermochemisty .…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) spectroscopy is an indispensable tool for organic, inorganic, and organometallic chemistry. NMR spectra can be measured for almost all elements and provide important information about the chemical environment. An accurate theoretical framework beyond the third row of the periodic table of elements necessitates the inclusion of special relativity. For instance, it was shown that selenium and tin NMR spectra are substantially affected by relativistic effects. This holds for both the chemical shift, describing the position of the signal, and the indirect spin–spin coupling constant (SSCC), describing the multiplet pattern.…”
Section: Introductionmentioning
confidence: 99%